Dual effect of dietary seaweed of extract nanoparticles (GNS) with bionanocomposite cellulose acetate membranes (CA/bio-AgNps) on growth performance and health status of the Nile tilapia (Oreochromis niloticus): Specification on feed utilization, immune system, and antiparasitic action - Radwan, Mahmoud; El-Sharkawy, Mahmoud A.; Negm, Mohammed A.; Mohammadein, Amaal; Malki, Jamila S. Al; Al-Thomali, Asma W.; Mohamed, Ahmed M.; Yassir, Shahd; Bashar, Mansour A.E. (Frontiers in Marine Science, 2022)
Seaweed draws a lot of attention for its vital role in aquaculture as it contains beneficial biological compounds that undoubtedly might help in the development of this field. The current study sheds light on the potential efficiency of dietary supplements of Grateloupia acuminata and G. doryphore (Halymeniaceae) nanoparticles (GNS) at different levels with bionanocomposite cellulose acetate membranes (CA/bio-AgNps) on improved growth performance, digestive enzyme activity, immunity, antioxidative, resistance against infectious pathogens, and characterization of water quality treated with CA/bio-AgNps that is used in rearing Nile tilapia (Oreochromis niloticus). Four concentrations (0.1, 0.25, 0.5, and 1.0 ml/L) of GNS extract were tested as potential anti-bacterial and for the efficacy of being parasitic. Fish with an average weight (24.46 ± 0. 50 g) were apportioned into six experimental groups (T0, T1, T2, T3, T4, and T5) represented as 0.0%, 0.0%, 0.1%, 0.25%, 0.5%, and 1.0% GNS in diets with CA/bio-AgNps, respectively. Injection of fish with Aeromonas hydrophila was performed at the end of the trial. Chemical and bacteriological water indices significantly showed improvement after being treated with CA/bio-AgNps than the control group. Growth, carcass composition, digestive enzyme, and hematological and biochemical indices were significantly noticed positive (p< 0.05), especially T4 and T5, than the control group. In parallel, a significant improvement was noticed in serum lysozyme, total immunoglobulin, complement C3, antioxidative enzyme, and the relative expression of hepatic and inflammatory genes with an increased level of GNS (p< 0.05) are upregulated than the control group. Remarkably, GNS-supplemented diets and extracts provided positive efficacy against A. hydrophila with a decreased percentage of fish mortality, besides efficacy on antibacterial strains and Cichlidogyrus tilapiae, respectively. To sum up, the seaweed extract with CA/bio-AgNps resulted in better growth performance of fish, antipathogenic effect, and health status. Furthermore, CA/bio-AgNps were vital in improving water characteristics. They should be studied and applied more in the future.